Comparison of flow structures in spacer-filled flat and annular channels - Ranade, Vivek V.; Kumar, Anil (Desalination, 2006)
Spacers are designed to create directional changes in the flow through membrane modules. Such secondary flow structures reduce concentration polarization and membrane fouling. Obviously, type of the spacer used in membrane modules strongly influences the resulting flow and therefore performance of the module. In this work, we have modeled detailed fluid dynamics of spacer filled channels by using the `unit cell' approach. The validated computational fluid dynamics (CFD) model was used to evaluate performance of certain spacer shapes and compare the resulting fluid dynamics in flat and curved channels. The simulations show that fluid flow behavior in a spacer-filled flat and a spiral channel was not significantly different. This means that pressure drops and mass transfer coefficients measured in flat channels may provide adequate guidelines, which would also be valid for spiral-wound modules. The results presented in this work will have significant implications for identifying improved spacers with higher propensities to reduce fouling in membrane modules.
International Congress on Membranes and Membrane Processes, Seoul, SOUTH KOREA, AUG 21-26, 2005
Keywords: annular channel; CFD; flat channel; membrane spacers

Eulerian-lagrangian simulations of unsteady gas-liquid flows in bubble columns - Buwa, Vivek V.; Deo, Dhanannjay S.; Ranade, Vivek V. (International Journal of Multiphase Flow, 2006)
We studied the dynamics of gas-liquid flows in a rectangular bubble column using Eulerian-Lagrangian simulations. Three-dimensional, unsteady simulations were performed to simulate the dynamic characteristics of the oscillating bubble plume. The effect of superficial gas velocity and aerated liquid height-to-column width (HI K) ratio on the dynamic and time-averaged flow properties was studied and the simulated results were validated using wall pressure and voidage fluctuation measurements. The effect of lift force and numerical diffusion on the dynamic and time-averaged properties is discussed in detail. Further, the results obtained using the Eulerian-Lagrangian simulations were compared with the Eulerian-Eulerian simulations. The bubble scale information, which is otherwise lost in the Eulerian-Eulerian simulations, was validated using the voidage fluctuation measurements. Such experimentally validated Eulerian-Lagrangian models will be useful for the simulation of mass transfer and reactions in bubble columns. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; CFD; Dynamics; Eulerian-Eulerian simulations; Eulerian-Lagrangian simulations; gas-liquid flow

Modeling of bubble column slurry reactor for reductive alkylation of p-phenylenediamine - Chaudhari, Amit S.; Rampure, Mohan R.; Ranade, Vivek V.; Jaganathan, Rengaswamy; Chaudhari, Raghunath V. (Chemical Engineering Science, 2007)
A bubble column slurry reactor (BCSR) model has been developed for the reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) to N, N'-di-secondary-alkyl-p-phenylenediamine (Di-amine). This particular reaction system is commercially relevant and involves a combination of parallel and consecutive reactions comprising equilibrium non-catalytic (homogeneous) and catalytic (heterogeneous) steps. The proposed model is based on the `mixing cell approach'. In this work the mixing cell approach has been extended by including a liquid backflow stream from all but the bottommost mixing cell. The model incorporates the contributions of gas-liquid and liquid-solid mass transfer, heat effects, and complex multistep reaction kinetics. CFD model is used to estimate the extent of backflow among mixing cells and its dependence on operating parameters. The effect of gas and liquid velocities, catalyst loading, inlet PPDA concentration, and temperature on the conversion, selectivity, global rate of hydrogenation, and temperature rise is discussed. The comparison of the current approach with the traditional mixing cell model is discussed. The BCSR model presented here will be useful to provide guidelines for designing and improving overall performance of bubble column reactors. (C) 2007 Elsevier Ltd. All rights reserved.
8th International Conference on Gas-Liquid and Gas-Liquid-Solid Reactor Engineering, Indian Inst Technol Delhi, New Delhi, INDIA, DEC 16-19, 2007
Keywords: bubble columns; CFD; kinetics; Mathematical modeling; Reductive alkylation

Singlejet fluidized beds: experiments and CFD simulations with glass and polypropylene particles - Utikar, Ranjeet P.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
Understanding hydrodynamics of bubbling fluidized beds is crucial in proper design and scale up of these beds. CFD models have shown promise in gaining this understanding. In order to generate confidence in CFD models, predicted time averaged and dynamical characteristics of the bubbling fluidized beds need to be validated against experimental data. This paper describes such studies with rectangular fluidized beds operated with a central jet. Digital image analysis and analysis of wall pressure fluctuations were used for this characterization. Fluidization of two types of particles, glass and polypropylene (PP) was studied at two different initial bed heights of H/D = 1 and 2 with three central jet velocities 5, 10 and 20 m/s. Time averaged as well as dynamical characteristics were studied. The Eulerian-Eulerian two fluid model based on kinetic theory of granular flows was used to simulate these experiments. The predicted results were compared with the experimental data and previously published correlations. Although, there is agreement with experimental data in some aspects, complete agreement was not found. The presented experimental data and comparison with CFD predictions will provide useful basis for further work on understanding bubbling fluidized beds. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; fluidized beds; hydrodynamics; image analysis; pressure fluctuations; single jet

CFD modeling of rotary cement kilns - Mujumdar, Kaustubh S.; Ranade, Vivek V. (Asia-Pacific Journal of Chemical Engineering, 2008)
Rotary cement kilns are widely used to convert calcineous raw meal into cement clinker, and are key components in the cement industry. In this article, we report a comprehensive computational fluid dynamics (CFD)-based model to capture key transport processes in rotary cement kilns. Separate but coupled computational models were developed for the bed and the freeboard regions of the rotary kiln. The complex swirling airflow produced by kiln burners, coal combustion, gas-phase combustion of volatile matter and radiative heat transfer in the freeboard region were modeled. The clinkerization reactions in the bed region were modeled assuming solids as pseudo fluids. Coating formation in cement kilns (for both bed and freeboard regions) was considered. Appropriate source and sink terms were developed to model transfer of CO(2) from the bed to the freeboard region due to calcination reaction in the bed region. The developed bed and freeboard models were coupled by mass and energy communication through common interface. These coupled computational models were able to quite satisfactorily predict the available data from industrial kilns and previously published results. The computational models were also able to capture the intricacies of the burning zones of rotary cement kilns for changing burner-operational parameters like axial to swirl ratio and oxygen enrichment. The developed approach, computational models and simulation results will not only help in developing better understanding of cement kilns but also provide quantitative information about influence of burner design and other design parameters on kiln performance. (C) 2008 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: burner; CFD; coal combustion; rotary cement kiln

Hysteresis in cloud heights during solid suspension in stirred tank reactor: experiments and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Aiche Journal, 2010)
Solid suspension in stirred tank reactor is widely used in process industries for catalytic reactions, dissolution of solids, crystallization, and so on. Suspension quality is a key issue in design and operation of stirred reactor and its determination is not straight forward. Cloud height measurements of solid suspension provide a relatively simple way to quantify quality of suspension. In this work, experiments were carried out to quantify variation of cloud heights with impeller speed and particle characteristics. These measurements were carried out using visual observations, image analysis, and ultrasound velocity profiler techniques. The obtained data demonstrated the existence of hysteresis in cloud heights with respect to impeller speed. Apart from possible applications in reducing power required for achieving desired solid suspension quality, the existence of hysteresis also provides a new way to evaluate computational fluid dynamics (CFD) simulations of solid liquid flows in stirred vessels. An attempt was made to capture observed hysteresis in cloud heights in CFD simulations. The simulated results were compared with the experimental data. The presented models and results (experimental and computational) will he useful for simulating complex solid liquid flows in stirred reactors. (C) 2010 American Institute of Chemical Engineers AIChE J, 56: 2795-2804, 2010
Keywords: CFD; hysteresis in cloud height; solid velocity profiles

CFD simulation of stirred tanks: comparison of turbulence models (Part II: axial flow impellers, multiple impellers and multiphase dispersions) - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
In the first part of the review, published literature regarding the CFD modelling of single-phase turbulent flow in stirred tank reactors with radial flow impellers was critically analysed. A brief overview of different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model and large eddy simulation) as well as impeller baffle interaction models has been presented in the previous part. This part is concerned with the review of literature regarding CFD simulation of axial flow impellers. Comprehensive simulations have been carried out using various turbulence models and the model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. The strengths and weaknesses of various turbulence models for axial flow impellers is presented. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-e model as well as Reynolds stress model. Literature efforts on multiple impeller systems and multiphase systems have been discussed in a separate section. Based on these results, suggestions have been made for the future work in this area.
Keywords: axial flow impellers; CFD; impeller models; stirred vessel; turbulence models

CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel

Solid suspension in stirred tanks: UVP measurements and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
Suspension of solids in stirred reactor is widely used for catalytic reactions, dissolution, etc. Quality of solid suspension is an important parameter required for the reliable design, optimum performance, and scale up of the system. Quality of suspension depends on local characteristics of solid velocity and hold up profiles. The present work was focused on investigating quality of solid suspension using ultrasound velocity profiler (UVP) measurements and CFD simulations. The slip velocity measurements carried out with UVP were used to evaluate different drag correlations used in CFD simulations. Results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.
Keywords: CFD; drag coefficient; solid suspension; solid-liquid velocities; UVP

Crystallization: key thermodynamic, kinetic and hydrodynamic aspects - Vedantam, Sreepriya; Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)
Crystallization is extensively used in different industrial applications, including the production of a wide range of materials such as fertilizers, detergents, food and pharmaceutical products, as well as in the mineral processing industries and treatment of waste effluents. In spite of the wide-spread use of crystallization, a clear understanding of the thermodynamic, kinetic and hydrodynamic aspects of the design methodologies are not yet well established. More often than not crystallization is still considered an art especially in fine-chemicals, pharmaceuticals and life-sciences sector. It is essential to understand and relate key thermodynamic, kinetic and hydrodynamic aspects to crystallizer performance, not just in terms of yield but also in terms of product quality (characterized by particle size distribution, morphology, polymorphism and the amount of strain as well as the uptake of solvent or impurities in the crystal lattice). This paper attempts to do that by critically reviewing published experimental and modelling studies on establishing and enhancing state-of-the-art thermodynamic, kinetic and hydrodynamic aspects of crystallization. Efforts are made to discuss and raise points for emerging modelling tools needed for a flexible design and operation of crystallizers and crystallization processes that are needed to meet the ever increasing demand on precise product specifications. Focus is on bringing out the trends which can be used as perspectives for future studies in this field.
Keywords: CFD; Crystallization; growth; Nucleation; polymorphism; supersaturation

Flow in vortex diodes - Pandare, Aditya; Ranade, Vivek V. (Chemical Engineering Research & Design, 2015)
A vortex diode is used as a cavitation device for treatment of industrial waste water and also, as a leaky non-return valve in nuclear applications. It consists of a vortex chamber with an axial and tangential port. When the fluid is injected through the tangential port, a strong vortex flow is set up in the diode chamber. This flow is characterized by phenomena such as vortex transition, precessing vortex core, toroidal recirculation zone, reverse flow core and recirculation zone in the axial port. Although studies have been conducted on the ``confined vortex'' class of flows (and some of them on vortex diodes), none of them provides a collective account of key nuances of the flow in a vortex diode. The flow in the diode differs from other confined-vortex flows on account of the axial-velocity deficit, due to which, direct correlations from other confined vortex flows cannot be applied to the diode. This work attempts to address the aforementioned flow characteristics in the diode using results primarily from CFD simulations. The reported methodology, computational model and results will be useful to gain better understanding of flows in vortex diodes and to optimize designs of vortex diodes for variety of applications. (C) 2015 Published by Elsevier B.V. on behalf of The Institution of Chemical Engineers.
Keywords: CFD; Confined vortex; Diode; Precessing vortex core; Recirculation

Two-phase flow boiling in 19mm tube: experiments and CFD modelling - Sardeshpande, Madhavi V.; Raymond, Barlev; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2016)
Boiling flows are encountered in a wide range of industrial applications such as boilers, nuclear reactors, electronic cooling, and various types of chemical reactors. Heat transfer coefficients, flow boiling regimes, flow instabilities, pressure drops, and conditions like dry-out are some of the key issues in every boiling flow study. It is observed that a limited experimental database is available for the 19mm ID channel diameter, i.e. a typical tube diameter of steam generator. Therefore, in the present work, the experimental setup was designed for studying boiling flows in a 19mm ID tube in such a way that different flow regimes occurring in a steam generator tube (from pre-heating of sub-cooled water to dry-out) could be investigated by varying inlet conditions. The reported results cover a reasonable range: 8-27kW/m(2) and 2.9-5.9kg/m(2)s heat and mass flux conditions, respectively. A basic computational flow model was also developed to facilitate interpretation of the obtained data. The presented design of the experimental setup and the approach of mimicking different types of steam generator tubes as well as presented experimental and simulated results are useful for gaining insight into complex boiling flows in tubes, and provide a sound basis for further work in this area.
Keywords: CFD; Flow regimes; two-phase flow boiling; vapour quality

CFD modelling of almond drying in a tray dryer - Chilka, Amarvir G.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
Drying is important in many food processing applications, and particularly so in the dry fruits industry. This work is focused on developing computational models for simulating the drying of almonds in a tray dryer. It is important to quantitatively understand heat and mass transfer within and around a single almond particle as well as the particle-particle interactions and their implications for dryer design. In this work, we have developed a systematic CFD modelling framework for modelling almond drying in a tray dryer. A single tray filled with almonds (similar to 2 kg) were dried at three set temperatures viz., 55, 65, and 75 degrees C. Air relative humidity at the inlet and outlet locations, and the weight of almonds were measured during drying for each experiment. An additional set of experiments were conducted in which almonds were filled only in the half section of the tray, keeping the other half empty. The same amount of almonds were used, to have multiple layers of almonds in the tray, and the set temperature for the experiment was 75 degrees C. Flow, heat, and mass transfer in the tray dryer were simulated using commercial CFD software Ansys Fluent. The validated computational model was used to simulate various cases including larger and more trays. The developed approach and models will be useful to select the appropriate dryer configuration and optimize its design. The developed models will also be useful to identify suitable operation conditions for the drying of almonds as well as other food products.
Keywords: Almonds; CFD; Drying; scale-up; tray dryer

Flow, mixing, and heat transfer in fluidic oscillators - Khalde, Chirag M.; Pandit, Ajinkya V.; Sangwai, Jitendra S.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
There is an increasing emphasis on process intensification and development of compact, intensified reactors and separators in recent years. Significant efforts are being made to develop such intensified reactors and separators without any moving parts. Some of the recent research studies have proven that a liquid-liquid extractor based on the Coanda effect and feedback oscillations exhibit excellent mixing and liquid-liquid contacting. These fluidic oscillators can potentially be used for a variety of other multiphase reactions and systems demanding enhanced mixing and heat and mass transfer. In this work, we have computationally investigated flow, mixing, and heat transfer in fluidic oscillators based on the Coanda effect. Available information on flow and mixing in fluidic oscillators was critically reviewed and key gaps in the available knowledge with respect to the design and optimization of fluidic oscillators were identified. Computational flow models were developed to characterize key flow features like unsteady flows, secondary vortices, and internal recirculation over a range of Reynolds number (Re = 90-1538) for three different oscillator designs. Systematic numerical studies were carried out to quantify different flow regimes, oscillations, and the influence of key geometric parameters on flow, mixing, and heat transfer. Simulated results were critically analyzed and are presented in the form of dimensionless numbers. The approach and results presented in this work will provide useful insights and a systematic basis for extending the applications of the Coanda-based feedback oscillatory devices for a wide range of engineering applications.
Keywords: CFD; Coanda effect; fluidic oscillators; heat transfer; mixing